1999
DOI: 10.1038/sj.ijo.0800962
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity with physical activity, television programs and other forms of video viewing among children in Mexico City

Abstract: OBJECTIVE: To assess the association of physical activity, television program viewing and other forms of video viewing with the prevalence of obesity among school children. DESIGN: Cross-sectional study. SUBJECTS: 712 children, 9 ± 16 y old, from a low-and a middle-income town in the Mexico City area. MEASUREMENTS: Children completed a self administered questionnaire to assess time spent in physical activity and television viewing, and diet. Height weight and triceps skinfolds were measured. The outcome variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
222
7
33

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(284 citation statements)
references
References 27 publications
(35 reference statements)
18
222
7
33
Order By: Relevance
“…This result is consistent with a growing body of evidence that, among children and adolescents, inactivity (particularly watching TV) is associated with body fatness in cross-sectional (Andersen et al, 1998;Hernandez et al, 1999;Tremblay and Willms, 2003), longitudinal (Maffeis et al, 1998;Berkey et al, 2000) and intervention studies Robinson, 1999). Obesity in children has even been reported to correlate in a dosedependent manner with baseline daily duration of television viewing in longitudinal observations (Dietz and Gortmaker, 1985;Gortmaker et al, 1996), suggesting a cause-effect relationship.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is consistent with a growing body of evidence that, among children and adolescents, inactivity (particularly watching TV) is associated with body fatness in cross-sectional (Andersen et al, 1998;Hernandez et al, 1999;Tremblay and Willms, 2003), longitudinal (Maffeis et al, 1998;Berkey et al, 2000) and intervention studies Robinson, 1999). Obesity in children has even been reported to correlate in a dosedependent manner with baseline daily duration of television viewing in longitudinal observations (Dietz and Gortmaker, 1985;Gortmaker et al, 1996), suggesting a cause-effect relationship.…”
Section: Discussionsupporting
confidence: 86%
“…The absence of a significant relationship between physical activity and OW found in the preadolescent and adolescent groups is only partially shared in the literature. Crosssectional and longitudinal studies are roughly divided between finding no effect (McMurray et al, 1995;Goran et al, 1997;Maffeis et al, 1998;Kimm et al, 2001), or a protective effect of activity (Moore et al, 1995;Hernandez et al, 1999;Berkey et al, 2000;O'Loughlin et al, 2000;Tremblay and Willms, 2003;Janssen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…76 Low levels of physical activity and greater amounts of sedentary pursuits, in particular television viewing (43 h/ days), during childhood and/or adolescence is predictive of greater future adiposity and or overweight. [77][78][79][80][81][82][83][84] Thus, the rationale for prescribing exercise as an adjunct to dietary restriction is compelling given its potential to reduce overweight-related comorbidity and the hazard associated with dietary restriction alone.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies linking the convergence of these two trends have demonstrated that high levels of TV use are significantly associated with child overweight. [3][4][5][6] The average American household with children aged 8-18 years has three TV sets, and 68% of children have a TV in their own bedroom. 2 Averaging at least 3 h a day, child media exposure to TV exceeds other media, including exposure to videos/DVDs/movies, print media, audio media, computers and video games.…”
Section: Introductionmentioning
confidence: 99%
“…2 High amounts of TV use have been associated with many negative outcomes, including poor scholastic performance, 7,8 sleep deprivation, 9,10 child requests for advertised foods, 11 eating fewer fruits and vegetables and more pizza/snack food/soda, 12 greater consumption of high-fat foods 13 and higher BMI. [4][5][6]14 Overweight is associated with many diseases, 1,[15][16][17] and the greater the degree of overweight as a child, the greater the likelihood that child will be overweight as an adult. 18,19 Extensive research addressing the intersection of TV use and child overweight has included known risk factors for child overweight, such as sociodemographics (e.g., gender, ethnicity, household income, parent education), 20,21 dietary intake (amounts and types of foods eaten), 13 presence of TV at meals, 12 perception of parental weight status 5,20 and measures of physical activity.…”
Section: Introductionmentioning
confidence: 99%